Symposium 3: What is it like for a learner to participate in a Zoom Breakout Room session? - Healey-Benson, Felicity; Johnson, Mike; Adams, Catherine; Turville, Joni (Proceedings of the International Conference on Networked Learning, 2024)
Though virtual classrooms are not new, the COVID-19 pandemic sent many teachers and students online for the first time. This paper examines the use of a web-based video conferencing tool, Zoom, and in particular, the use of breakout rooms as part of a student’s learning experience. We ask: what is it like for a learner to participate in a Zoom Breakout Room session? Using Max van Manen’s (2016) phenomenology of practice, we collected learners’ lived experience descriptions of participating in a Zoom breakout room, then reflected on them phenomenologically as a way to generate new insights into this recently common online learning experience. Four moments are portrayed: a learner’s arrest at the announcement of breakout rooms; a learner’s transition into a breakout room as existential suspension; surveilling self and others in a breakout room; and exiting the breakout room as a moment of foreclosure and re-disorientation. The paper compares Zoom breakout rooms with aspects of video-gaming and notices a detriment to Freirean problem-posing education if students can avoid standing, unmediated, behind just their words, even in the relative safety of a small group of peers.